2019
DOI: 10.1088/1755-1315/322/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Modeling of Effective Series Resistance for Lithium-ion Batteries under Life Cycle Consideration

Abstract: This paper presents a modeling of effective series resistance for Lithium-ion batteries, which is focusing on the effect of life cycles in aging cells during operations. A computer-based sequential control system is developed to prepare aging cells and automatically characterize the information of testing batteries. Several aspects of testing parameters during the charge and discharge, such as characteristics of the effective series resistance, amplitudes of the pulse current, changes of the increasing resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…By introducing two heating mechanisms into a thermal model and utilizing artificial neural networks to capture the relationship between temperature and state of charge for effective prediction, this algorithm has low time complexity and strong adaptability. Somakettarin et al proposed an effective series resistance model to study the relationship with battery life [37], resulting in small estimation errors. It can serve as a novel indicator for evaluating the health status of lithium-ion batteries.…”
Section: Discussionmentioning
confidence: 99%
“…By introducing two heating mechanisms into a thermal model and utilizing artificial neural networks to capture the relationship between temperature and state of charge for effective prediction, this algorithm has low time complexity and strong adaptability. Somakettarin et al proposed an effective series resistance model to study the relationship with battery life [37], resulting in small estimation errors. It can serve as a novel indicator for evaluating the health status of lithium-ion batteries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tests of Sony LIBs were carried out, stored at temperatures of 20 and 60 C, which showed that in the case of potentiostatic maintenance of 4.2 V, capacity losses during the year amounted to 23%, of which 18% were irreversible losses. Storage under normal temperature conditions and constant charge maintenance increase the rate of LIB degradation, while at elevated temperatures this factor is not so critical [107]. In addition, exceeding the threshold value of the charging voltage or a long-term charge of LIB at a voltage of 4.2 V has an extremely negative effect on the performance of the battery.…”
Section: Degradation Processes In a Lithium-ion Batterymentioning
confidence: 99%
“…But in 2020, the mileage of electric cars increased to 300-500 km after the release of Tesla cars. In this regard, there is still a tendency to increase the maximum range of electric cars, and accordingly, the change in battery capacity and daily mileage [19].…”
Section: Introductionmentioning
confidence: 99%